Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(x^3-2x^2+3x-6=x\left(x^2+3\right)-2\left(x^2+3\right)=\left(x-2\right)\left(x^2+3\right)\)
b, \(x^2+2x+1-4y^2=\left(x+1\right)^2-\left(2y\right)^2=\left(x+1-2y\right)\left(x+1+2y\right)\)
\(A=x^2-7xy+12y^2\)
\(A=x^2-3xy-4xy+12y^2\)
\(A=x\left(x-3y\right)-4y\left(x-3y\right)\)
\(A=\left(x-4y\right)\left(x-3y\right)\)
\(B=x^2-3xy-4y^2\)
\(B=x^2+xy-4xy-4y^2\)
\(B=x\left(x+y\right)-4y\left(x+y\right)\)
\(B=\left(x-4y\right)\left(x+y\right)\)
\(A=x^2-7xy+12y^2\)
\(=x^2-3xy-4xy+12y^2\)
\(=x\left(x-3y\right)-4y\left(x-3y\right)\)
\(=\left(x-4y\right)\left(x-3y\right)\)
\(2x^2y^3-\frac{x}{4}-4y^6\)
đây là pt bậc 2 của y^3 , ta đặt y^3=z ta được
\(-\left(4z^2+\frac{2.2xz}{2}+\frac{x^2}{4}\right)+\left(\frac{x^2}{4}-\frac{x}{4}\right)\)
\(-\left(2z+\frac{x}{2}\right)^2+\left(\frac{x^2}{4}-\frac{x}{4}\right)\)
\(-\left\{\left(2x+\frac{x}{2}\right)^2-\left(\frac{x^2}{4}-\frac{x}{4}\right)\right\}\)
\(-\left\{\left(2x+\frac{x}{2}+\sqrt{\frac{x^2}{4}-\frac{x}{4}}\right)\left(2x+\frac{x}{2}-\sqrt{\frac{x^2}{4}-\frac{x}{4}}\right)\right\}\)
1) \(x^3+x^2+4\)
\(=\left(x^3-x^2+2x\right)+\left(2x^2-2x+4\right)\)
\(=x\left(x^2-x+2\right)+2\left(x^2-x+2\right)\)
\(=\left(x^2-x+2\right)\left(x+2\right)\)
2) \(x^3-2x-4\)
\(=\left(x^3+2x^2+2x\right)-\left(2x^2+4x+4\right)\)
\(=x\left(x^2+2x+2\right)-2\left(x^2+2x+2\right)\)
\(=\left(x^2+2x+2\right)\left(x-2\right)\)
x2-8xy+15y2 +2x-4y-3
= (x-4y)2 - y2 + (2x-8y) +4y -3
= (x-4y)2 +2(x-4y) +1 - y2+4y-4
= (x-4y+1)2 -(y-2)2 = (x-3y-1)(y-5y+3)